Pengenalan Pasar Kawak Melalui Media Sosial untuk Meningkatkan Eksistensi oleh KKN 189 UNS - Waluyo, Budi; Maradheta, Amartya Afra; Damayanti, Amelia; Rahmadhani, Fitria Suci; Pangestu, Hafidh Rian; Fitriyanti, Ira; Kirana, Indah Ratna; Puspita, Kezia Ayuni; Putri, Nanditya Vianti; Tama, Pasya Yauga Danial Eka; Putri, Restu Gista (Nanggroe: Jurnal Pengabdian Cendikia, 2024)
Pasar Kawak is a traditional market located in Dukuh Ngasinan Etan, Gebang Village, Masaran District, Sragen. Pasar Kawak offers various types of traditional culinary, such as brambang asem, pecel pincuk, sego uleng, cendol dawet, and many more. Not only that, Pasar Kawak also presents various traditional entertainment in it, such as gejog lesung, traditional music, reog, and so on. This study aims to increase the existence of Pasar Kawak through social media and the creation of historical plaques. The methods used include information preparation, plaque creation, and article publication. The results are historical plaques installed around the market and articles about Pasar Kawak are published on social media, in order to increase the existence of Pasar Kawak to the wider community. This program is expected to increase the existence of visitors to Pasar Kawak as a center of local economy and culture in Sragen.